Prenatal genetic diagnosis of omphalocele by karyotyping, chromosomal microarray analysis and exome sequencing - Shi, Xiaomei; Tang, Hui; Lu, Jian; Yang, Xiue; Ding, Hongke; Wu, Jing (Annals of medicine (Helsinki), 2021)
The aim of this study is to share our experience in the prenatal diagnosis of omphalocele by karyotyping, chromosomal microarray analysis (CMA) and whole exome sequencing (WES). In this retrospective study, 81 cases of omphalocele were identified from 2015 to 2020. Associated anomalies and prenatal diagnosis based on karyotyping, CMA and WES were analysed. Fifty-eight (71.6%) of the 81 foetuses had other ultrasound anomalies. Giant omphalocele was present in 11 cases (13.6%) and small omphalocele was present in 70 cases (86.4%). Chromosomal abnormalities were found in 24 foetuses (29.6%, 24/81), the most common of which were trisomy 18 (58.8%, 11/24) and trisomy 13 (29.2%, 7/24). Compared to isolated omphalocele, non-isolated omphalocele was accompanied by an increased prevalence of chromosomal abnormalities (4.3% (1/23) vs. 39.7% (23/58), χ 2 = 8.226, p = .004). All chromosomal abnormalities were found in small omphalocele. Aside from aneuploidy, CMA showed one pathogenic copy number variants (CNVs) for a detection rate of 1.2%, one variants of unknown significance (VOUS) and one instance of loss of heterozygosity (LOH). WES was performed on 3 non-isolated cases, and one was found to have pathogenic variants. The most common genetic cause of omphalocele is aneuploidy and the prevalence of chromosomal abnormalities is increased with non-isolated and small omphalocele. CMA and WES can be useful for providing further genetic information to assist in prenatal counselling and pregnancy management.